"Making something new": rethinking genre in the end times. Issue 2 (3rd April 2022) - Flynn, Bailey
ABSTRACT: Rhetorical Genre Studies has been a productive subfield of communication studies since the 1980s, with the conceptualization of "apocalyptic" as a genre being one influential outcome. Literature on the topic has explored apocalypse as a genre arising to make sense of destabilizing events that fit within no pre-existing symbolic framework. I join this conversation with a slight shift in focus, from the genre itself to the destabilization that occasions it and its potential for rhetorical invention. Picking up on Lauren Berlant's theorization of the "genre flail, " I argue that the flail can be an ambivalent and productive rhetorical space where reparative and radical rhetorics may gain ground in addition to or beyond apocalyptic and violent alternatives. My case study in end times here is the global climate crisis as depicted in the 2018 film Annihilation . Through rhetorical analysis of the film's mixed-genre style and ambivalent narrative, I define two possible readings of the film: as diagnostic and as social ecology. These dual readings demonstrate the creativity of genre flail, its potential as a rhetorical zone of innovation, and the importance of interrogating the destructive and reparative genres of practice it produces as potential ways of living-with environmental end times.